ASSESSMENT OF SOME LOCAL AND IMPROVED SWEET POTATO (Ipomoea batatas (L.) Lam.) VARIETIES FOR GROWTH AND YIELD POTENTIAL IN OWERRI, IMO STATE, NIGERIA. (Wudil Journal of Science and Technology Education, 2025)
The experiment was conducted at the Federal University of Technology Owerri Research farm between the end of May – the end September of 2024, with the aim of assessing some local and improved sweet potato varieties for growth and yield potential. Each variety was planted in a 3m × 3m (9m2) plot size, at a planting distance of 1.0m ×0.3m. The experiment was laid out in Randomized Complete Block Design with three replications and separated from each other at a space of 1m. Vine cuttings were planted on ridges and poultry manure was applied at four weeks after plantingat the rate of 3.2t/ha. Data for growth and yield parameters were collected and subjected to Analysis of variance and means separation was done using Least Significant Difference (LSD). The Analysis of Variance showed Significant differences (p
Keywords: Sweet potato, Varieties, Assessment, Growth, Yield.